+0  
 
0
169
1
avatar

How do you solve -6-3y=27 with work ?

Guest Mar 22, 2017
Sort: 

1+0 Answers

 #1
avatar+4749 
+2

The main thing you have to remember is whatever you do to one side of the equation, you must do to the other side to keep the equation true.

-6 - 3y = 27

 

Add 6 to both sides. The 6 on the left side goes away when you add 6.

-3y = 27 + 6

 

-3y = 33

 

Divide both sides by -3. The -3 on the left side goes away when you divide by -3.

y = 33/(-3)

 

y = -11         Now it is solved for y. :)

hectictar  Mar 22, 2017

8 Online Users

We use cookies to personalise content and ads, to provide social media features and to analyse our traffic. We also share information about your use of our site with our social media, advertising and analytics partners.  See details